A Maximum Power Point Tracking Algorithm for Photovoltaic Systems under Partially Shaded Conditions - Archila Valderrama, John Edinson (2016)
This paper shows a modification of the traditional ‘perturb and observe’ algorithm used to the maximum power point tracking in photovoltaic systems. The proposal is justified by the need of algorithms to track the global maximum power point in solar panels connected in series under partially shaded conditions. The proposal tracks the global maximum power point avoiding the previous iterative search in local maximums. The algorithm performance is evaluated by simulations in the software PSIM and its behavior is compared with the traditional perturb and observe algorithm. The results show the outstanding performance of the modified algorithm in the tracking of the global maximum power point under different no uniform conditions of temperature and irradiance in the solar array.